AGROCHEMICAL ANALYSIS OF SOILS IN PRECISION FARMING TECHNOLOGIES: A CASE STUDY OF THE CHERNIHIV REGION - ZATSERKOVNYI, Vitaliy; VOROKH, Victor; HLOBA, Olga; MIRONCHUK, Tetiana; SIUIVA, Iryna (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Precision agriculture aims to create a comprehensive decision-support system that enhances the efficiency and sustainability of agricultural practices. It is based on the principle that fields are not homogeneous and consist of various zones with distinct characteristics. Variability in soil, terrain, climatic conditions, and other factors results in different plant requirements across different field zones. Precision agriculture allows for consideration of this variability, enabling an individualized approach for each field section. A research presents a comprehensive approach to analyzing all key stages of agrochemical surveys, from the preparatory phase to laboratory analysis, the development of agrochemical maps, as well as the creation of fertilizer requirement maps and task maps for agricultural machinery. Particular attention is paid to the potential use of remote sensing data and geographic information technologies for processing and visualizing results. Methods. Soil sampling begins with determining the configuration and area of elementary zones. Several soil sampling strategies are considered, allowing each agricultural enterprise to choose the most suitable one based on its goals and specific field conditions. Agrochemical soil properties can vary significantly even within small field areas, necessitating a meticulous approach to sampling for analysis. Results. Developed agrochemical maps serve as additional visual materials that modern laboratories provide along with agrochemical soil reports. These maps, available in both paper and digital formats, illustrate various levels of humus content, nutrient levels in the soil, and soil solution pH. Conclusions. Agrochemical soil analysis provides essential information for optimizing the processes of differential fertilizer and seed applications. Based on the data obtained about soil type, macro- and micronutrient content, organic matter levels, moisture levels, and other key indicators, the nutrient requirements of elementary zones can be accurately determined. This enables the development of effective agronomic strategies tailored to specific field conditions.